2018
DOI: 10.20452/pamw.4246
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the gut microbiota in adult patients with type 1 and 2 diabetes based on the analysis of a fragment of 16S rRNA gene using next-generation sequencing.

Abstract: Introduction Scientific data indicate a possible influence of gut microbiota on the development of type 1 and type 2 diabetes mellitus (T1DM and T2DM, respectively). Sequence analysis of 16S ribosomal RNA identified several hundred bacterial species of the intestinal ecosystem, most of which cannot be cultured. Objectives We aimed to evaluate gut microbiota composition in adult patients with T1DM and T2DM and establish a link between microbiological test results and patients' clinical data. Patients and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
58
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 22 publications
19
58
3
1
Order By: Relevance
“…In the work by Salamon et al, after sequencing isolates from stool samples, a similar relationship, but one of average severity, was observed in both patients with type 1 (r = 0.46; p = 0.03) and type 2 (r = 0, 43; p = 0.03) diabetes [21]. These observations confirm the relationship between the genus of Bifidobacterium and HDL concentration in animal studies [22][23][24].…”
Section: Discussionsupporting
confidence: 65%
“…In the work by Salamon et al, after sequencing isolates from stool samples, a similar relationship, but one of average severity, was observed in both patients with type 1 (r = 0.46; p = 0.03) and type 2 (r = 0, 43; p = 0.03) diabetes [21]. These observations confirm the relationship between the genus of Bifidobacterium and HDL concentration in animal studies [22][23][24].…”
Section: Discussionsupporting
confidence: 65%
“…However, the authors did not analyze the influence of the treatment type on the observed change in mycobiota. Similar results were obtained by Standaert-Vitse et al (2009) where CD patients were more frequently and more heavily colonized by C. albicans than the patients in the control group. As it was found in our study, the group undergoing biologic therapy showed significantly higher colonization with Candida spp.…”
Section: Discussionsupporting
confidence: 84%
“…The increasing occurrence of Crohn's disease and the decreasing age of patients stimulate researchers to find out the causes behind this illness (Benchimol et al 2017;Ng et al 2017). Although, until now, it has not been possible to associate a particular microorganism with CD etiology, microbial participation is still considered crucial, besides genetic and immunological disorders, for induction or intensification of inflammation in the gastrointestinal tract (Gosiewski et al 2012;Wright et al 2015). However, there is still insufficient knowledge concerning the role of fungi in the course of CD, as well as the impact of the treatment on gastro-intestinal colonization with fungi of the genus Candida in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations